Effects of vitamin C and exercise on lipid profile, platelet and erythrocyte indices in young soccer players - Karakilcik, A. Z.; Halat, R.; Zerin, M.; Çelik, H.; Nazligul, Y. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: Exercise may increase production of reactive oxygen species (ROS) enhancing oxidative stress. Antioxidants can efficiently scavenge ROS before they initiate oxidative damage of biomolecules such as enzymes, nucleic acids, lipids and lipoproteins in the body. Vitamin C, an important antioxidant, may affect oxidative stress in living organism. Therefore, this study was carried out to investigate the effects of exercise and vitamin C on thiobarbituric acid-reactive substance (TBARS), lipid profile, erythrocyte and platelet indices in young soccer players.